Irritable bowel syndrome - Enck, Paul; Aziz, Qasim; Barbara, Giovanni; Farmer, Adam D.; Fukudo, Shin; Mayer, Emeran A.; Niesler, Beate; Quigley, Eamonn M. M.; Rajilić-Stojanović, Mirjana; Schemann, Michael; Schwille-Kiuntke, Juliane; Simren, Magnus; et al. (Nature reviews. Disease Primers, 2016)
Irritable bowel syndrome (IBS) is a functional gastrointestinal disease with a high prevalence. Enck et al. describe the association between IBS and other gastrointestinal, somatic and psychiatric conditions, as well as the current view on the pathophysiology, and diagnostic and management options.